2019
DOI: 10.1111/nph.15637
|View full text |Cite
|
Sign up to set email alerts
|

Endocytosis acts as transport pathway in wood

Abstract: Summary In trees, dead and living cells of secondary xylem (wood) function collectively, rendering cell‐to‐cell communication challenging. Water and solutes are transported over long distances from the roots to the above‐ground organs via vessels, the main component of wood, and then radially over short distances to the neighboring cells. This enables proper functioning of trees and integrates whole‐plant activity. In this study, tracer loading, immunolocalization experiments and inhibitor assays were used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 90 publications
1
19
0
Order By: Relevance
“…Another important factor to consider is the speed at which host defence signalling macromolecules can travel, which is likely to be extremely limited in parenchyma alone; to keep pace with advancing decay or pathogen-related mycotoxins would demand a faster apoplastic route. Utilising vessels for long-distance signalling transport could meet defence demands, but this requires a depositary system from vessel-associated cells (parenchyma in contact with vessels) into vessels and possibly the retrieval of defence proteins along-route, which involves apoplastic to symplastic transport as suggested by Słupianek et al (2019).…”
Section: Sapwood As a Three-dimensional Structure In Relation To Defencementioning
confidence: 99%
“…Another important factor to consider is the speed at which host defence signalling macromolecules can travel, which is likely to be extremely limited in parenchyma alone; to keep pace with advancing decay or pathogen-related mycotoxins would demand a faster apoplastic route. Utilising vessels for long-distance signalling transport could meet defence demands, but this requires a depositary system from vessel-associated cells (parenchyma in contact with vessels) into vessels and possibly the retrieval of defence proteins along-route, which involves apoplastic to symplastic transport as suggested by Słupianek et al (2019).…”
Section: Sapwood As a Three-dimensional Structure In Relation To Defencementioning
confidence: 99%
“…It is also comprised of the three major components, vessels, fibers and parenchyma cells formed by the activity of the cambium. It should be noted that vessels are often surrounded by small living cells, the paratracheal parenchyma, which has important functions in the transport of compounds for example in Populus tremula x tremuloides, Fraxinus excelsior and Acer pseudoplatanus [15].…”
Section: What Makes the Stem?mentioning
confidence: 99%
“…Although this process is not yet fully understood, there is substantial evidence that paratracheal parenchyma cells also designated as vessel-associated cells (VACs) play an important role in this process [71]. As stated earlier, VACs are living cells surrounding the xylem vessels, which makes them ideal candidates to facilitate the refilling process [15]. To refill the vessels with water, a change in the osmotic gradient between VACs and vessel cells is indispensable.…”
Section: Drought Leads To Major Transcriptional Remodellingmentioning
confidence: 99%
“…Słupianek et al . () showed that endocytosis is an active process required for the transport of macromolecules from vessels into neighboring ‘vessel‐associated cells’. Their results help to provide a comprehensive picture of transport within wood, including not only the movement of water, but also the long distance transport of macromolecules axially through the tree, followed by the uptake and radial transport of cargo within the living parenchyma of wood.…”
Section: Structure and Function Of Woodmentioning
confidence: 99%